Health-related quality of life in robotic versus open radical prostatectomy - Rush, Stacy; Alibhai, Shabbir M.H.; Xu, Lizhen; Xu, Wei; Louis, Alyssa S.; Matthew, Andrew G.; Nesbitt, Michael; Finelli, Antonio; Fleshner, Neil E.; Hamilton, Robert J.; Kulkarni, Girish; Zlotta, Alexandre; et al. (Canadian Urological Association Journal, 2015)
Introduction: It is unclear whether health-related quality of life (HRQoL) outcomes are superior in robot-assisted radical prostatectomy (RARP) compared to open prostatectomy (ORP). Methods: We retrospectively analyzed records from men who received ORP or RARP at our institution between January 2009 and December 2012. Patients completed a demographics questionnaire and the Patient-Oriented Prostate Utility Scale (PORPUS), a validated disease-specific HRQoL instrument prior to surgery and every 3 months up to 15 months after surgery. Results: In total, 974 men met the inclusion criteria (643 ORP and 331 RARP patients). At baseline, RARP patients were significantly younger (p < 0.001), had lower body mass index (BMI) (p < 0.001), lower preoperative prostate-specific antigen (PSA) (p < 0.001), fewer comorbidities (p < 0.004), and higher baseline PORPUS scores (p = 0.024). On follow-up, unadjusted PORPUS scores were significantly higher in the RARP group at each point. On multivariable analysis adjusting for age, ORP versus RARP procedure, Gleason score, BMI, first PSA, comorbidity, ethnicity, and baseline PORPUS scores, PORPUS score was higher for the RARP group at 3 months (p = 0.038) and 9 months (p = 0.037), but not at 6, 12, and 15 months (p = 0.014). No difference met pre-defined thresholds of clinical significant. Conclusions: Though unadjusted HRQoL outcomes appeared improved with RARP compared to ORP differences, adjusted differences were seen at only 2 of 5 postoperative time points, and did not meet pre-defined thresholds of clinical significance. Further randomized trials are needed to assess whether one treatment option provides consistently better HRQoL outcomes.